A comparative study between dexmedetomidine and propofol for maintaining depth of anesthesia in elective craniotomy: a prospective randomized double blind study - Roy, Amrita; Sarkar, Suman; Chatterjee, Anirban; Banerjee, Anusua (International Journal of Research in Medical Sciences, 2017)
Background: The objective of present study was to assess the efficacy of dexmedetomidine over propofol in maintaining depth of anesthesia in patients undergoing elective craniotomy. Methods: Ninety patients of American Society of Anaesthesiologists (ASA) physical status 1 or 2, of either sex, with Glasgow Coma Score (GCS) 14 or 15, scheduled for elective craniotomy, were allocated in two groups, Group D and Group P. Each group consisted of 45 patients. Anesthesia was induced with propofol and maintained with nitrous oxide in oxygen, atracurium and intermittent fentanyl. Patients in Group D received continuous infusion of dexmedetomidine 0.4 µg/kg/hour which was started after induction and stopped after closure of dura in and patients in Group P received continuous infusion of propofol 100 µg/kg/min in same manner. Heart Rate (HR), mean arterial pressure (MAP), and bispectral index (BIS) were recorded and compared at specific time points which are known to have hemodynamic alterations throughout the intraoperative period. Results: Dexmedetomidine was comparable and even better (after intubation p 0.02, head pin fixation p 0.00, opening of dura p <0.00) than propofol in maintaining depth of anesthesia. It also attenuated HR and MAP at intubation, head pin fixation, skin incision, making of burr hole, opening of dura and at extubation (p 0.00). But Ramsay sedation score of patients after extubation in both groups did not differ significantly (p 0.36). No patient had recall. Conclusions: Dexmedetomidine is comparable with propofol in maintaining depth of anesthesia during elective craniotomy. It can be used as a sole anesthetic agent during craniotomy.